The relationship between muscle mass and fat content in body composition and non-alcoholic fatty liver disease in the Chinese general population: a cross-sectional study - Xu, Guoqiong; Wu, Yuanyuan; Chen, Jie; Xiang, Dan; Li, Dongji (Frontiers in Medicine, 2024)
Introduction: Non-alcoholic fatty liver disease (NAFLD) poses a significant global health challenge, necessitating comprehensive exploration of its etiology. This study investigates the intricate relationship between body composition and NAFLD prevalence, focusing on the balance between muscle mass and fat content. Methods: Employing a retrospective cross-sectional design, 2,493 participants undergoing routine health examinations were analyzed. Body compositions, including muscle mass and fat, were measured using bioelectrical-impedance analysis. The prevalence of NAFLD was assessed based on clinical guidelines. Results: This study included 2,493 patients, including 1,601 (64.2%) men and 892(35.8%) women. The average age of these participants was 46.0±13.1 years, with a mean body mass index of 25.0±3.6 kg/m2. The levels of fat free mass (FFM) to fat mass (FM) ratio (FFM/FM) and appendicular skeletal muscle mass index (ASMI) demonstrated a negative association with the prevalence of NAFLD (OR (95% CI): 0.553 (0.427-0.704) and 0.850 (0.730-0.964), P<0.001 and P=0.022, respectively). Liver function further elucidates the multifaceted impact of body composition on hepatic health. In contrast to other parameters, FFM/FM displayed a negative association with liver damage indicators, including a negative association with alanine aminotransferase (Beta±SE: -1.00±0.17, P< 0.001), with aspartate aminotransferase showing borderline significance (Beta±SE: -0.26±0.15, P=0.084). Similar associations were also evident in terms of liver productive function and bilirubin metabolism. Conclusion: Our study offers novel insights into the nuanced interplay between body composition and NAFLD. Recognizing the significance of the balance between muscle and fat provides a foundation for tailored interventions that may reshape the landscape of NAFLD prevention and management.